People’s sovereignty in the digital sphere: Challenging conventional legislation - Muhammad Safaat Gunawan; Eki Furqon (Privietlab, 2026)
The role of social media is far more massive, becoming a space for articulating the aspirations of the people that influence the legislative process in Indonesia. The wave of rejection of the KPK Law, the Job Creation Law, the new Criminal Code, and even the Constitutional Court's decision reveals a paradox: the sovereignty of the people, which is guaranteed by Article 1 paragraph (2) of the 1945 Constitution, is actually stronger in the digital space than in the formal forum of the House of Representatives. Conventional legislative mechanisms are elitist, closed, wasteful of budget, and even prone to corruption, prompting the public to seek alternative channels through online petitions, hashtags, and digital demonstrations. This phenomenon raises fundamental questions about the legitimacy of formal legislation when the aspirations of the people are actually stronger in cyberspace. This study uses a normative legal method with the analytical tools of Habermas' deliberative democracy theory, digital sovereignty, and digital political participation. An international comparative study (United States, United Kingdom, Estonia, and India) shows that digital democracy can be institutionalized through official mechanisms such as e-petitions, e-voting, and online public consultations. This paper offers the concept of digital constitutional democracy, namely the integration of digital space as an official channel for public participation in lawmaking. Several breakthroughs include the digitization of Prolegnas (E-Prolegnas), a permanent public aspiration portal, digital signature verification, and the establishment of an independent supervisory body to maintain the validity of aspirations. These breakthroughs are believed to be capable of cutting down on conventional legislative practices that are elitist and wasteful, while strengthening constitutional legitimacy. Thus, Indonesian democracy can transform into a participatory, transparent, and adaptive legislative model in line with technological developments, while maintaining people's sovereignty in the digital era.